2023
DOI: 10.1038/s41598-023-32810-2
|View full text |Cite
|
Sign up to set email alerts
|

Expedited diagnosis of pediatric tuberculosis using Truenat MTB-Rif Dx and GeneXpert MTB/RIF

Abstract: Rapid, cost-effective, and sensitive diagnostic assays are essential for global tuberculosis (TB) control, especially in high TB burden, resource-limited settings. The current study was designed to evaluate diagnostic accuracy of Truenat MTB-Rif Dx (MolBio) in children less than 18 years of age, with symptoms suggestive of TB. Gastric aspirate, induced sputum, and broncho-alveolar lavage samples were subjected simultaneously to AFB-smear, GeneXpert MTB/RIF, liquid culture (MGIT-960) and Truenat MTB-Rif Dx. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Truenat MTB-RIF-Dx does not detect the rpoB Q432K and S441L mutations [110]. However, these mutations are rare, with less than 0.7% frequencies globally [110][111][112].…”
Section: Chip-based Real-time Micro Pcr Assaysmentioning
confidence: 93%
“…Truenat MTB-RIF-Dx does not detect the rpoB Q432K and S441L mutations [110]. However, these mutations are rare, with less than 0.7% frequencies globally [110][111][112].…”
Section: Chip-based Real-time Micro Pcr Assaysmentioning
confidence: 93%
“…This Made in India product approved by the World Health Organization (WHO) is a classical demonstration of the practical applications of DH. [28][29][30] Mobile applications are also used to help rural healthcare providers identify and refer possible TB patients to the nearest microscopy center. 31 The author is the Principal Investigator of a pilot study in two remote districts in the state of Gujarat for technologically enabled TB screening using handheld X-ray machines and TrueNat on-site diagnostics.…”
Section: Sanjeevani Appmentioning
confidence: 99%
“…The tests are run using a near-POC dual-instrument system for the detection of MTB and reflex-based detection of rifampicin resistance. A recent study in India demonstrated that when using pediatric specimens including gastric aspirate, induced sputum, and bronchoalveolar lavage, sensitivity and specificity were comparable to the results obtained using Xpert assays [ 87 ].…”
Section: Evaluating Children With Presumptive Tbmentioning
confidence: 99%